Neonicotinoid contamination in conservation areas affects bees more sharply than beetles - Tetlie, Jonathan; Harmon-Threatt, Alexandra (Frontiers in Ecology and Evolution, 2024)
The neurotoxic insecticide class of neonicotinoids has become one of the most widely used groups of pesticides globally. Their long half-lives and high water solubility increase their potential to linger and affect numerous organisms long after application. A prominent concern associated with residual contamination is the negative impact that neonicotinoids can have on beneficial arthropods such as bees and certain groups of beetles. Many studies have looked at the effects neonicotinoids have on arthropod communities in lab settings; however, comparatively few studies have looked at these groups in neonicotinoid-contaminated restored prairie habitats. These habitats are often restored from or located near agriculture and are almost ubiquitously contaminated with neonicotinoids. Our one-year manipulated field study compared native bee nesting rates and beetle community assemblages between paired clothianidin-contaminated and non-contaminated restored prairie plots. Native bee nesting probability and nesting abundance increased by 46% and 172%, respectively, in sites contaminated with clothianidin. Conversely, we observed no significant differences in beetle family assemblages, abundance, or richness between clothianidin-contaminated and control sites. These results suggest that neonicotinoid contamination of natural habitats can have numerous environmental consequences for arthropods and that these effects are not always consistent between taxa. Understanding how neonicotinoid contamination affects beneficial groups such as bees and arthropod community assemblages is crucial for characterizing the risks these chemicals pose to ecologically imperative taxa.Deleted: However, several beetle feeding guild abundances 37 and trophic interactions between feeding guilds were 38 influenced by clothianidin contamination. Deleted: As an unintended consequence of their extensive 84 use, natural areas and restoration habitats are frequently 85 contaminated with neonicotinoids 86 Deleted: , 87 Deleted: which 88 Deleted: Much of the neonicotinoid contamination research 89 in natural areas has primarily focused on nectar and pollen 90 contamination, as these represent a potential route of 91 exposure to economically and ecologically important 92 pollinators (Rundlöf et al., 2015). However, neonicotinoids 93 also have the propensity to accumulate in the soil and persistfor extended periods of time (Rexrode et al., 2003).